2011
DOI: 10.1093/ndt/gfr475
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of Bartter syndrome in Korea

Abstract: Twenty-three (88.5%) of the 26 BS patients involved in this study had CLCNKB mutations. The p.W610X mutation and large deletion were two common types of mutations in CLCNKB. The clinical manifestations of BS III were heterogeneous without a genotype-phenotype correlation, typically manifesting cBS phenotype but also aBS or mixed Bartter-Gitelman phenotypes. The molecular diagnostic steps for patients with BS in our population should be designed taking these peculiar genotype distributions into consideration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 35 publications
7
54
1
4
Order By: Relevance
“…5,21 By contrast, the clinical manifestations of type III BS and GS may vary and resemble each other. 7,[11][12][13] Furthermore, p-BS/GS is difficult to distinguish from type III BS or GS because its clinical features match those of the latter two diseases. Correctly distinguishing these three diseases based on their clinical characteristics is thus important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,21 By contrast, the clinical manifestations of type III BS and GS may vary and resemble each other. 7,[11][12][13] Furthermore, p-BS/GS is difficult to distinguish from type III BS or GS because its clinical features match those of the latter two diseases. Correctly distinguishing these three diseases based on their clinical characteristics is thus important.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of type III BS were previously reported to show features similar to those of GS, including hypomagnesemia and hypocalciuria. 7,[11][12][13] In addition, one report published in 2003 showed that, in a large consanguineous family, both the BS and GS phenotypes were present with the same CLCNKB mutation. 13 In the same year a review article pointed out the phenotypic overlaps between type III BS and GS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). Olgumuzda KCNJ1 gen dizi analizinde hastalığa neden olan mutasyon saptanmazken; SLC12A1 gen dizi analizine bakılamadı.…”
Section: Discussionunclassified
“…Neonatal BS amniyon sıvısında klor yüksekliğiyle beraber açıklanamayan polihidramniyoz ve prematür doğum öyküsü, poliüri, tuz kaybı ve ciddi dehidratasyonla karakterize ağır bir hastalık olup; 1,2/100,000 sıklıkta görülmektedir (1)(2)(3)(4)(5). Neonatal BS, Henle kulpunun çıkan kalın kolundaki tübüler epitelyum hücrelerinde eksprese olan SLC12A1 ve KCNJ1 genlerindeki mutasyonlar sonucu gelişmektedir (6). Tedavi elektrolit imbalansı ve dehidratasyonun düzeltilmesi, prostaglandin sentetaz inhibitörlerinin kullanılmasından ibarettir.…”
Section: Introductionunclassified